Standardization of Requirements for Culture Media Used to Assess the Quality of Drugs (Review) - S. M. Sukhanova (Разработка и регистрация лекарственных средств, 2023)
Introduction. A reliable assessment of the quality and safety of medical products (MP) by biological indicators is directly related to the use of culture media (CM) that meet the established requirements. However, when conducting trial, it is necessary to take into account the peculiarities of culture media due to the presence in their composition of components of biological origin. In particular, a high degree of variability and unstable stability of raw materials, as well as possible mistakes in producing and storage of media, create the prerequisites for deviations. The use of industrial culture media also does not guarantee their suitability for the appropriate test. Therefore to obtain reliable results, the compliance of each batch CM with the specified criteria be confirmed must be confirmed by standard methods using the full range of meaningful indicators. The current lack of a state standard in the Russian Federation regulating the requirements for the use of culture media when confirming the quality of medical products makes it much more difficult to assess the suitability, comparability and reliability of the analysis results, both themselves CM and drugs.Text. The article discusses the draft General Pharmacopoeia Article (GPM) "Culture media", which presents the general requirements for of culture media when used in pharmacopoeia analysis. The standard is intended for specialists involved in the development, improvement and application of methods and / or techniques necessary for confirming the properties of medical products for the purpose of registration, entry into civil circulation, as well as in their production. The document was drawn up taking into account modern domestic and international approaches of good pharmaceutical practices to the assessment of the drugs that involve the use of culture media. The project identifies the key factors that most affect the quality of culture media. Based on the principle of continuity, compiled and described in detail a set of standardized control methods, including tests on physical-chemical and biological indicators. For exploring of specific properties, there are requirements for test cultures have been established. Governs special requirements for culture media used to obtain biological medical products are regulated. The procedure for storage and disposal of culture media unsuitable for use is described.Conclusion. The introduction of the GPM "Culture media" into the practice of domestic pharmacopoeic analysis will increase the reliability of the results of the evaluation of the effectiveness and safety of drugs, and as a result will lead to a reduction in production risks and risks of harm to health patients during in pharmacotherapy and immunoprophylaxis. The proposed approaches can also be used in other branches of science and industry.